KAJIAN EFISIENSI BIAYA PELAKSANAAN PROYEK DENGAN PEMANFAATAN LIMBAH CANGKANG SAWIT PADA PROSES DRYER AMP (Studi Kasus : Peningkatan Jalan Ruas Tumbang Talaken-Tumbang Jutuh Kalimantan Tengah) - Miftah Ardiyansah; Ismiyati Ismiyati; Syafrudin Syafrudin (Politeknik Negeri Semarang, 2022)
Infrastructure Improvement which is located on Jl.Tumbang Talaken - Jl.Tumbang Jutuh with a length of 40,920 meters and a distance of 141 km to the capital city of Palangka Raya. The condition of the remote location and the fluctuating price of diesel fuel will require large costs. While around the project is an oil palm plantation and the waste is piling up. If left untreated, palm shell waste will have a negative impact and cause disease, by utilizing palm shell waste as a dryer heater in Hotmix production as a substitute for diesel fuel with the hotmix production cost efficiency analysis method on AMP so that it can reduce production costs in the project. The results of the analysis of validity and reliability show that production by gasifying palm shell waste is feasible to replace diesel fuel. The results of the BEP analysis, that the use of shells as a substitute for diesel fuel has great potential to reduce production costs, when hotmix production is at a volume of 3,826 tons. So, with a planned hotmix production volume of 22,667 tons, it is feasible to procure or invest in shell combustion equipment. Suggestions from this study that replacing dryers with palm shell waste material as a substitute for diesel fuel can be done if the road infrastructure development project is around oil palm plantations, because in addition to being able to reduce hotmix production costs on AMP it is also an environmentally friendly waste management because it has no impact negative on the environment. If the project is not located in the vicinity of an oil palm plantation, then the use of palm shell waste as a substitute for diesel fuel needs to be further researched because the efficiency value will be different